The relationship between visual spatial working memory capacity of tennis players and visual information processing of offensive tactical decision-making - Cheng, Y.; Wang, N. (Frontiers in Psychology, 2026)
Objective: To investigate how spatial working memory (SWM) ability and visual search features influence tennis players` offensive tactical preemptive decision-making.